Periodontal plastic surgery associated with treatment for the removal of gingival overgrowth - Bosco, Álvaro Francisco [UNESP]; Bonfante, Samara [UNESP]; Luize, Danielle Shima [UNESP]; Bosco, Joseane Maria Dias [UNESP]; Garcia, Valdir Gouveia [UNESP] (Wiley, 2006)
Background: Excisional biopsies of gingival overgrowths, performed with safety margins, frequently result in mucogingival defects. These defects may produce esthetic problems and increase the chances of dentin hyperesthesia and its possibility of hindering oral hygiene. Methods: Two clinical cases are reported in which gingival overgrowths were removed by excisional biopsy, resulting in unsightly defects. The first clinical case presents an invasive approach for the treatment of a recurrent pyogenic granuloma in the anterior maxilla, and the second depicts a complete removal of a peripheral odontogenic fibroma in the posterior maxilla. In both situations, the soft-tissue defects were repaired by periodontal plastic surgery, including a laterally positioned flap and a coronally positioned flap, respectively. Results: Periodontal plastic surgery successfully restored the defects that resulted from biopsies, and no recurrence has been noticed in the 5-year postoperative follow-up period. Conclusions: The combination of biopsy and periodontal plastic surgery in a one-step procedure seems to be suitable to remove gingival overgrowths in most areas of the mouth, regardless of esthetic significance. Such procedures seem to restore gingival health, encourage healing, and create both esthetics and function in the excised area.
Keywords: Biopsy; Esthetics; Fibroma; Grafts; Granuloma; Plastic surgery; adolescent; adult; case report; esthetics; female; fibroma; follow up; gingiva overgrowth; gingival biopsy; human; maxilla tumor; odontogenic tumor; plastic surgery; postoperative care; pyogenic granuloma; soft tissue defect; surgical approach; tissue flap; wound healing; biopsy; gingiva tumor; pathology; reoperation; Adolescent; Adult; Female; Gingival Neoplasms; Gingival Overgrowth; Granuloma, Pyogenic; Humans; Odontogenic Tumors; Reoperation